Thinking eyes: visual thinking strategies and the social brain - van Leeuwen, Janneke E. P.; Crutch, Sebastian J.; Warren, Jason D. (Frontiers in Psychology, 2023)
The foundation of art processes in the social brain can guide the scientific study of how human beings perceive and interact with their environment. Here we applied the theoretical frameworks of the social and artistic brain connectomes to an eye tracking paradigm with the aim to elucidate how different viewing conditions and social cues influence gaze patterns and personal resonance with artworks and complex imagery in healthy adults. We compared two viewing conditions that encourage personal or social perspective taking — modelled on the well-known Visual Thinking Strategies (VTS) method — to a viewing condition during which only contextual information about the image was provided. Our findings showed that the viewing conditions which used VTS techniques directed the gaze more towards highly salient social cues (Animate elements) in artworks and complex imagery, compared to when only contextual information was provided. We furthermore found that audio cues also directed visual attention, whereby listening to a personal reflection by another person (VTS) had a stronger effect than contextual information. However, we found no effect of viewing condition on the personal resonance with the artworks and complex images, when taking the random effects of the image selection into account. Our study provides a neurobiological grounding of the VTS method in the social brain, revealing that this pedagogical method of engaging viewers with artworks measurably shapes people’s visual exploration patterns. This is not only of relevance to (art) education, but also has implications for arts-based diagnostic and therapeutic applications.